Accelerated, Neuronavigated Neuromodulation for Negative Symptoms in Schizophrenia: Protocol for a Randomized Controlled Pilot Trial - Choucroun, Ashley; Roy, Olivier; Potvin, Stéphane; Palaniyappan, Lena; Zeramdini, Nadia; Aiyaar, Aryamman; Picard, Katherine; Zanjani, Samaneh; Parekh, Deven; Markessinis, Mariza; Friesen, Timothy; Zamorano, Tihare; et al. (Santé mentale au Québec, 2026)
Background Negative symptoms (NS) of schizophrenia, including avolition, anergia, and social withdrawal cause major functional impairment and have limited treatment options. Repetitive transcranial magnetic stimulation (rTMS) targeting the left dorsolateral prefrontal cortex (LDLPFC) shows promise in alleviating NS, though response remains modest, and multi-week protocols are often burdensome. A five-day, high-dose intermittent theta burst stimulation (iTBS) protocol using fMRI-guided neuronavigation has demonstrated rapid and sustained effects in major depression. Given the overlap between depressive lassitude and NS domains, accelerated neuronavigated iTBS may hold promise in schizophrenia with NS.Methods This multisite, randomized, patient- and rater-blinded trial evaluates the feasibility, safety, and preliminary efficacy of such a protocol in individuals with schizophrenia spectrum disorders. Seventy-five adults with clinically significant NS will receive either: (1) neuronavigated active iTBS targeting LDLPFC regions most anti-correlated with the subgenual anterior cingulate cortex (sgACC) (2) non-neuronavigated active iTBS using scalp-based coordinates; or (3) neuronavigated sham stimulation over 10 daily sessions spanning 5 consecutive days (90,000 pulses total), with follow-ups at 1 week, 1 month, and 3 months. Résultats Outcomes include a reduction in NS; Efficacy comparisons between neuronavigation and non-neuronavigation; Feasibility and safety; Change in social and affective information processing; Change in depressive symptoms.Conclusion Results will inform future trials, while comparison of targeting strategies will clarify the utility of neuronavigation. If successful, this trial will offer a time-efficient, personalized intervention for NS.